Quantifying Environmental Flow Requirement Towards Watershed Sustainability - Karakaya, Nusret; Evrendilek, Fatih (Asian Journal of Chemistry, 2012)
Humankind is prone to exceeding biogeochemical limits to freshwater resources in the face of rapidly increasing demands of global population and economic growth without a measurable indicator of sustainability. Such indicators with a differing methodological complexity were developed for rivers in order to estimate water quantity required to secure their long-term productive state. Generally, environmental flow requirement method was applied to economically significant rivers where intensive fisheries take place and was defined as the sum of flow requirements that fish stocks demand. Recently, more robust methods for environmental flow requirement have been developed that consider multiple environmental factors such as demands of other organisms (e.g., invertebrates and water birds), ecosystem structure (e.g., biogeoclimate, geomorphology, flora, fauna, biodiversity and flood plain) and ecosystem function (e.g., nutrient cycles, primary production and ecosystem respiration). This study assesses the concept of environmental flow requirement in the context of Big Melen water transfer project as a case study.